The length of maternity leave and its statutory pay as a determinant of women’s professional activity - Pasternak-Malicka, Monika (Wymiar urlopu macierzyńskiego związanego z pełnieniem osobistej opieki nad dzieckiem oraz wysokość zasiłku jako determinanty aktywności zawodowej kobiet, 2020)
The purpose of the paper is an attempt to assess the impact of the length of maternity leave as the basis for the payment of maternity allowance under social insurance and its statutory pay on the professional activity of women. The paper evaluates the relationship between the length of maternity leave and related payments of maternity allowance and the employment rate, and also tries to indicate whether extending maternity leave may limit women’s employment. The paper describes the professional activity of women, and the level of expenditure on childcare related benefits in Poland and in selected European Union countries. Based on statistical data, an attempt was made to assess the impact of maternity benefits on the economic activity of women based on the linear regression method. Some parts of the author’s own surveys from 2013-2020 were also presented. They suggest that extending maternity leave may discourage employers from taking on women and, consequently, lead to their withdrawal from the labour market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 56-70